Le fratture esposte articolari e periarticolari - Ciriello, V.; Combi, A.; Chiarpenello, R.; Piovani, L. (Lo Scalpello - Journal, 2019)
ARTICULAR AND PERIARTICULAR OPEN FRACTURESExposed articular and periarticular fractures are serious injuries, often resulting from high-energy traumas,associated to high risk of septic complications, functional impairment of the affected limb and not infrequentlypatient’s life threatening conditions. Their incidence, though low, is however increasing.The patient with exposed fracture presents an associated injury up to one third of cases. The initial evaluation plays afundamental role both in the identification and treatment of any concomitant injuries, and in the choice of strategyand timing of treatment of the exposed fractures. The presence of a plastic surgeon in the team facilitates thedefinition of the therapeutic path.The debridement of the lesion is a fundamental time and must be accurate. Stabilization with external fixator iscertainly the treatment of choice and can be adopted both as temporary or as a definitive fixation. Soft tissuemanagement is the keystone of the therapeutic pathway of exposed articular and periarticular fractures. The progressmade in “orthoplasty” encourages acute internal fixation and immediate coverage—fix and flap, with a significantreduction in infectious risks and improvement of prognosis.In any case, the available evidence about the treatment of these injuries is limited. Proper management requires amultidisciplinary approach, great experience and personalization of the therapeutic path.